Regeneración e integración urbana en el barrio Santa Fe (2021)
The project starts from an analysis of the mobility plans that are developed in Bogotá, in which it is evident that the Regiotram is an important mobility system for the region that is planned to be built in 2023. Within Bogotá, there are currently the rails of the old railroad, but they want to develop a connection in the Santa Fe neighborhood that could be generating a fragmentation in this, a neighborhood that currently due to its conditions such as insecurity problems, abandoned buildings, prostitution and others, were already generating fragmentation .